Surgical technique for superselective neck dissection under local anesthesia in recurrent head and neck cancer. Issue 8 (26th April 2022) - Kobayashi, Kenya; Ikeda, Atsuo; Matsumoto, Yoshifumi; Matsumura, Satoko; Omura, Go; Eguchi, Kohtaro; Sakai, Azusa; Ito, Akiko; Matsumoto, Fumihiko; Yoshimoto, Seiichi
Abstract: The aim of this paper is to describe a safe and effective surgical technique for neck dissection under local anesthesia. An increasing number of patients cannot undergo general anesthesia due to systemic complication arising from old age. Moreover, the long‐term survival of patients with recurrent or metastatic cancer due to advances in chemotherapy has increased the necessity of neck dissection under local anesthesia. Appropriate pain control and selection of medical devices are important factors for success of the surgery under local anesthesia. In addition to the usual subcutaneous infiltration anesthesia for pain control, nerve blocks for each cervical nerve encountered during surgery are extremely effective. Since muscle relaxants are not available, sharp devices such as knife or scissors, instead of electric scalpel, should be used to prevent unexpected muscle contractions caused by electric current. This video presents well‐proven techniques and technical tips for superselective neck dissection under local anesthesia. Abstract : This article supplements the Operative Techniques video presentation, which can be viewed online on Head & Neck's home page at http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)1097-0347